The Impact of Beverages on Ingestive Behavior - Casperson, Shanon L. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Nutrients is planning a Special Issue focusing on beverages and ingestive behavior. This Special Issue will focus on research related to all aspects of beverage consumption and post-ingestive consequences. There continues to be much controversy surrounding the influence of beverage choice on health outcomes. Research investigating the impact of beverage choice has on human health and post-ingestive consequences continue to grow. We know from the growing body of literature that beverage choice has a substantial impact on metabolism, food reinforcement and eating behaviors.